2023
DOI: 10.2989/16073606.2022.2146545
|View full text |Cite
|
Sign up to set email alerts
|

A pointfree theory of Pervin spaces

Abstract: A Pervin space is a set equipped with a bounded sublattice of its powerset, while its pointfree version, called Frith frame, consists of a frame equipped with a generating bounded sublattice. It is known that the dual adjunction between topological spaces and frames extends to a dual adjunction between Pervin spaces and Frith frames, and that the latter may be seen as representatives of certain quasi-uniform structures. As such, they have an underlying bitopological structure and inherit a natural notion of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Symmetrization is for Pervin spaces and Frith frames, what uniformization is for quasiuniform spaces and quasi-uniform frames, respectively. This has been considered in [19] for Pervin spaces and in [7] for Frith frames. In particular, it has been shown that the categories of symmetric Pervin spaces and of symmetric Frith frames are equivalent to the categories of transitive and totally bounded uniform spaces and frames, respectively.…”
Section: Symmetrizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Symmetrization is for Pervin spaces and Frith frames, what uniformization is for quasiuniform spaces and quasi-uniform frames, respectively. This has been considered in [19] for Pervin spaces and in [7] for Frith frames. In particular, it has been shown that the categories of symmetric Pervin spaces and of symmetric Frith frames are equivalent to the categories of transitive and totally bounded uniform spaces and frames, respectively.…”
Section: Symmetrizationmentioning
confidence: 99%
“…A filter F ⊆ P(X ) is a Cauchy filter if it is proper and, for every S ∈ S, either S or its complement is in F. We say that a Cauchy filter F converges to the point x ∈ X if every open neighborhood U ∈ S (X ) of x belongs to F. Finally, a Pervin space (X , S) is said to be Cauchy complete if every Cauchy filter converges, and a Cauchy completion of (X , S) is a dense extremal monomorphism c : (X , S) → (Y , T ) into a Cauchy complete Pervin space (Y , T ). 7 In the following, we refer to the symmetrization of a Pervin space, defined in Sect. 2.5.…”
Section: Complete Pervin Spaces and Complete Frith Framesmentioning
confidence: 99%
See 3 more Smart Citations